THE TECHNOLOGICAL HAZARD – A FACTOR FOR MODELING THE INDUSTRIAL CULTURAL LANDSCAPE IN OCNA MUREȘ - VASILIȚĂ-CRĂCIUN, Ileana-Cristina; NICULA, Gabriel; GAVRA, Camelia-Ina (Studia Universitatis Babeș-Bolyai Geographia, 2022)
It is well known that an exploitable resource is a potential factor of social attraction and economic development Thus, concretely the salt resource present in the underground of Ocna Mureș facilitated its exploitation from the first moments of discovery and the construction of a specific industry with the technological evolution at global level and finding out the various possibilities of processing and capitalization. At the same time, it brings into question the transformations that have taken place within the local cultural landscape, in a fortuitous and irreversible way with the chained manifestation of a complex of unforeseen factors in the form of hazards. Therefore, the study in question presents technological hazard as an opportunity for the emergence and development of new cultural elements designed to open up other possibilities for capitalization.